Optimization Of Crude Palm Oil Production Machine Scheduling Using The Campbell Dudek Smith (CDS) Method - Ratri Nurfitriah; Fibri Rakhmawati (Science and Technology Research Centre Universitas PGRI Semarang, 2024)
Palm oil production in Indonesia currently meets 40% of the world’s consumption needs. Control and planning of the production process in maximizing performance results that are useful for maximizing profits and minimizing losses can be archived through optimization and scheduling. One method that can be used in scheduling optimization is the Campbell Dudek Smith (CDS) method. By using the CDS algorithm, each treatment to be completed must go throught the work process on each production machine (flowshop) to get the minimum makespan value. This method can be used to sort jobs in the palm oil production process which is carried out at several stations. Where each machine works according to the production process sequence schedule. The results of the optimal job sequence in the palm oil production process using CDS are : J1 J2 J3 J4 J5 J6 J7 J8 J9 J10 J11 J12 J13 with an optimal makespan value of 404 minutes.